Personalized approach to diagnosis verification and pathogenetic therapy in benign breast diseases (literature review) - Tatyana Yu. Pestrikova; Elena A. Yurasova; Igor V. Yurasov; Olga G. Shcherbakova (LLC "MEDIAFORMAT", 2023)
The review presents data on the tactics of managing patients with benign breast diseases aimed at reducing the incidence of breast cancer. Particular attention is paid to the use of non-hormonal herbal preparations with a favorable safety profile, the components of which suppress the hyperproliferation of the mammary gland epithelium, lead to regression of cysts in its tissue, and reduce mammographic density, which is a protector of the development of malignant processes.